EVALUATION OF ZINC STATUS OF PRESCHOOL CHILDREN AS ASSESSED BY HAIR ZINC LEVEL IN PUNJAB PROVINCE: Zinc Status of Preschool Children - Vaqar, Abeer; Malik, Nazir Ahmed; Hafeez, Assad; Ashraf, Riffat Nisar; Hassan, Mumtaz (Pakistan Armed Forces Medical Journal, 2009)
Objectives: To determine status of zinc in healthy children in some parts of Punjab province by estimation of hair zinc levels. Study design: Descriptive study (cross sectional survey) Place and Duration of Study: The study was organized at KRL Hospital from August 2004 to January 2005. Study samples were selected randomly from a larger study (To evaluate vitamin A status) carried out in 6 districts of Punjab. Subjects and Methods: This community-based study was done in 6 districts of Punjab including Mianwali, Jhang, Attock, Multan, Pak Pattan and Faisalabad. The population selected was 1-5 yr old healthy children. Both male and female healthy children were included. Malnourished children with mid arm circumference < 12 cm, children with skin and hair disorders, liver disease and prolonged illnesses were excluded from the study. After parental consent and filling up of questionnaire data, hair samples were collected. Relevant features like age, sex, dietary history and previous illnesses were recorded. Hair samples were taken, sealed in dry plastic bags and dispatched to Dr A Q Khan Research Laboratories (KRL) Kahuta where they were analyzed using atomic absorption spectrophotometery. Data analysis was performed through SPSS-10.0. Results: Mean age of study population was 37.51 ± 13.39 months and male to female ratio was 1:1.32. Hair zinc levels ranged from 69 to 227 µgm/ gm of hair. Mean hair zinc level was 164.79 ± 53.7 µgm/gm of hair. Majority of children (62) had an adequate zinc level, while 13 were identified with low zinc status (<100 µgm/gm). Hair zinc was not significantly higher in children with adequate dietary habits, similarly there was no association with age and gender. Conclusion: Majority of healthy pre-school children in the sampled districts of Punjab did not have zinc deficiency as assessed by hair zinc level. However about 1 in 10 children was deficient in zinc even in the healthy population.